Teachers' perspectives on implementing cooperative learning to promote social and emotional learning - Karmina, Sari; Dyson, Ben; Setyowati, Lestari (LPMPP Universitas Negeri Yogyakarta, 2024)
Evidence has shown that social and emotional learning (SEL) improves students' behavior, attitudes, peer relationships, and academic outcomes. However, teachers have challenges in promoting SEL due to insufficient professional development and pedagogical strategies. Cooperative learning, a pedagogy promoting student-centered learning, has been suggested to help teachers foster students' SEL. However, little research has been conducted to investigate cooperative learning alignment with SEL. Thus, this current study explores teachers' perspectives on implementing cooperative learning to promote students' SEL. Seven elementary school teachers implementing cooperative learning and SEL in their classrooms joined the study. A qualitative interpretative case study design was used. Teacher interviews as primary data, and field notes, teachers' artefacts, lesson plans, and teaching videos were collected. Thematic analysis was used to analyze the data from the teacher interviews and field notes. Four themes were generated: group roles, exploring potentials and weaknesses, meaningful interactions, and consensus decision-making. The findings suggest that cooperative learning through clear group roles promotes elementary school students' self-awareness and social awareness, meaningful interactions, and consensus decision-making.